Symbols of Heroes in the Indonesian and Chinese Movies - Woro Januarti (Bina Nusantara University, 2021)
The research aimed to compare a movie with the theme of heroes from Indonesia and China concerning message related to heroes, hero images, ideology, and even heroic culture of the two countries. It explored 20 Indonesian and Chinese films with comparative literary perspectives related to the theme of heroism. The focuses of the research were (1) how could the image of the hero created by the film provide a view of each country’s people’s culture, (2) could the movies provided more detailed information on the policies of each country, and (3) how could films strengthen the relationship between Indonesia and China. The research applied a qualitative methods with a comparative literature perspective. The data source were from the dialogues in the film “Merah Putih”, “Gie”, “Susi Susanti”, “Soekarno”, “Tanah Surga Katanya”, “3 Srikandi”, “Laskar Pemimpi”, “Guru Bangsa”, “Soegija”, “Jenderal Soedirman”, 攀登者 (The Climbers), 中国机长 (The Captain), 红海行动 (Operation Red Sea), 烈火英雄 (The Bravest),战狼 1 (Wolf Warrior 1), 战狼 2 (Wolf Warrior 2), 建国大业 (The Founding of A Republic), 建党大业 (Beginning of The Great Revival), 建军大业 (The Founding of An Army), and 叶问 (IP Man). Data analysis technique were conducted by (1) determining variables, (2) classification, (3) analysis, and (4) conclusions. The results show that the symbols of heroism in Indonesian and Chinese films have similarities to the fight against colonialism, injustice, and class. The theme of heroism in the two countries’ films has a striking differences, such as Chinese films are more concerned with collective characters’ obligations and interests, the film does not have an element of humor, and the theme emphasizes conflicts with other countries. While Indonesia films highlight individual characters’ views and movies still include comedy and emphasize domestic problems.